Blunt head trauma in a peculiar case of partial mummification. Murder or accidental event?. (June 2022) - Barranco, Rosario; Castelletti, Lara; Fossati, Francesca; Zotti, Mirca; Orcioni, Giulio Fraternali; Verdiani, Simonetta; Ventura, Francesco
The finding of a partially mummified body presenting signs of trauma requires the forensic pathologist to conduct a careful and complex examination; multidisciplinary analysis is often necessary. We report a case where the partially mummified corpse of an elderly man was found in his own home more than seven years after death. Complete post-mortem investigation revealed a cranial fracture and an acute subdural haematoma. An in-depth multidisciplinary analysis provided important information on the modality and cause of death but it was not possible to establish whether the trauma and death resulted from an accidental event or from an assault.